Signals trigger state-specific transcriptional programs to support diversity and homeostasis in immune cells - Fischer, Cornelius; Metsger, Maria; Bauch, Sophia; Vidal, Ramon; Böttcher, Michael; Grote, Phillip; Kliem, Magdalena; Sauer, Sascha (Science signaling, 2019)
Macrophages play key roles in the immune systems of humans and other mammals. Here, we performed single-cell analyses of the mRNAs and proteins of human macrophages to compare their responses to the signaling molecules lipopolysaccharide (LPS), a component of Gram-negative bacteria, and palmitate (PAL), a free fatty acid. We found that, although both molecules signal through the cell surface protein Toll-like receptor 4 (TLR4), they stimulated the expression of different genes, resulting in specific pro- and anti-inflammatory cellular states for each signal. The effects of the glucocorticoid receptor, which antagonizes LPS signaling, and cyclic AMP-dependent transcription factor 3, which inhibits PAL-induced inflammation, on inflammatory response seemed largely determined by digital on-off events. Furthermore, the quantification of transcriptional variance and signaling entropy enabled the identification of cell state-specific deregulated molecular pathways. These data suggest that the preservation of signaling in distinct cells might confer diversity on macrophage populations essential to maintaining major cellular functions.
Keywords: THP-1 buňky; transkripční faktor ATF3; Signal Transduction; Humans; Interleukin-8; genetická variace; Single-Cell Analysis; makrofágy; regulace genové exprese; Homeostasis; signální transdukce; Gene Expression Regulation; Transcription, Genetic; Lipopolysaccharides; analýza jednotlivých buněk; THP-1 Cells; lipopolysacharidy; palmitany; Toll-Like Receptor 4; interleukin-8; Genetic Variation; Macrophages; lidé; toll-like receptor 4; Activating Transcription Factor 3; Palmitates; interleukin-1beta; Interleukin-1beta; homeostáza; genetická transkripce